Anais Estendidos Do XXIII Simpósio De Realidade Virtual E Aumentada (SVR Estendido 2021) 2021
DOI: 10.5753/svr_estendido.2021.17646
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Method for Investigating Finger-based Representations using Virtual Reality

Abstract: Finger use plays an important role in the development of cognitive (e.g., numerical) concepts. Such embodied relationship between fingers and numbers persists even into adulthood when fingers are typically no longer used for counting. Better understanding how this embodied relationship builds up and plays out is a relevant and ongoing endeavor. To help researchers on this subject, we propose a novel method to investigate finger-based representations using virtual reality. The system is based on virtual hands t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Recent studies have shown that this implicit representation of fingers can be experimentally biased by manipulating the hand posture: hence, the perceived number of fingers in-between two tactile stimulations decreases as the hand posture makes them appear closer to each other (Tamè et al, 2017). Virtual reality technologies provide another promising approach to modify finger counting experience by creating the illusion of fused or supernumerary fingers that participants can learn to use with minimal practice in an immersive environment (Souza et al, 2021). If finger counting makes the covert activation of fingers necessary to process numbers, normally developed adults should show atypical numerical performance after their finger representation is re-configured through virtual reality.…”
Section: The Need For Decisive Evidencementioning
confidence: 99%
“…Recent studies have shown that this implicit representation of fingers can be experimentally biased by manipulating the hand posture: hence, the perceived number of fingers in-between two tactile stimulations decreases as the hand posture makes them appear closer to each other (Tamè et al, 2017). Virtual reality technologies provide another promising approach to modify finger counting experience by creating the illusion of fused or supernumerary fingers that participants can learn to use with minimal practice in an immersive environment (Souza et al, 2021). If finger counting makes the covert activation of fingers necessary to process numbers, normally developed adults should show atypical numerical performance after their finger representation is re-configured through virtual reality.…”
Section: The Need For Decisive Evidencementioning
confidence: 99%